Bioactive Ingredients in Traditional Fermented Food Condiments: Emerging Products for Prevention and Treatment of Obesity and Type 2 Diabetes - Alphonse Laya; Honoré Wangso; Iva Fernandes; Raphaël Djakba; Joana Oliveira; Eugenia Carvalho (Journal of Food Quality)
Obesity and type 2 diabetes (T2D) are severe metabolic diseases due to inappropriate lifestyle and genetic factors and their prevention/treatment cause serious problems. Therefore, searching for effective and safe approaches to control obesity and T2D is an essential challenge. This study presents the knowledge regarding the possible use of traditional fermented condiments (TFC), a known major source of bioactive compounds (BACs), as an adjuvant treatment for obesity and T2D. Data on antiobesity, antidiabetic, and different mechanisms of BACs action of TFC were collected using a methodical search in PubMed, Scopus databases, Web of Science, SciELO, and the Cochrane Library. We discuss the mechanisms by which BCs prevent or treat obesity and T2D. The effects of TFC on obesity and T2D have been found both in animal, human, and clinical studies. The findings demonstrated that BACs in TFC confer potential promising antiobesity and antidiabetic effects. Because of the potential therapeutic significance of bioactive ingredients, the consumption of TFC could be recommended as a functional condiment. Nevertheless, further investigation is required in more clinical studies of TFC to support the formulation of functional fermented condiments and nutraceutical and pharmaceutical applications.